Effect of under-floor air distribution system to prevent the spread of airborne pathogens in classrooms - Chang Heon Cheong (Elsevier, 2021)
This study investigated the effect of the under-floor air distribution (UFAD) system compared to conventional mixed-mode ventilation system to prevent airborne pathogen spread in elementary school. To analysis airborne pathogen spread pattern, STAR-CCM+ is used. By applying the UFAD system airborne infection risk at region around the exhaust area of conventional ventilation system can be significantly reduced. However, increased infection risks around exhaust area of UFAD system still existed. Thus, it is recommended to install the exhaust vents (outlets) away from the breathing area. In addition, since both of conventional ventilation system and the UFAD systems have a high infection risk at the front of the classroom, novel method to reduce the infection risk from students to teachers should be considered.